Synthesis of the agrifood systems’ hidden costs analysis in the six FABLE country case studies - Vittis, Yiorgos; Mosnier, Aline; Smith, Alison; Arguello, Ricardo; Chavarro Diaz, John; Costa, Wanderson; Köberle, Alexandre; Singh, Vartika; Getaneh, Yonas; Nigussie, Yirgalem; Navarro, Javier; Sperling, Frank; et al. (FABLE Consortium, 2024)
This chapter summarizes the main findings about hidden costs in agrifood systems across six countries, Australia, Brazil, Colombia, Ethiopia, India, and the United Kingdom building on the results from SOFA 2023, the FABLE Consortium, and the Food System Economic Commission (FSEC) initiative. While the fact that unhealthy diets currently trigger the biggest hidden costs in most countries was a surprise for some stakeholders, there was a consensus that this is an important and growing issue that urgently needs to be addressed. Changing diets and increasing agricultural productivity have the largest impact on reducing the agrifood system’s hidden costs in the future, but implementing an integrated strategy that can also target environmental protection has the largest benefits. Some hidden costs related to undernourishment are covered in the analysis, but they do not accurately reflect the size of the problem, particularly in low-income and lower-middle-income countries. Better local datasets should be used in hidden costs computation for GHG emissions and land cover change, and thresholds for poverty and undernourishment should be aligned with national statistics. There are challenges to communicating the complexity of the hidden costs method, but this topic is gaining momentum for policy planning, and several governments are already either utilizing or planning to develop similar metrics, so this analysis was a timely exercise.